1987
DOI: 10.1128/aac.31.12.2007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of OHIO-1 beta-lactamase

Abstract: A total of 31 plasmids, all bearing a gene that encodes a novel, plasmid-mediated Richmond-Sykes class III beta-lactamase designated OHIO-1 and a gene that encodes aminoglycoside 2"-adenyltransferase, have been collected from hospitals in Ohio. By using restriction endonuclease digestion and Southern hybridization, we were able to demonstrate that all these plasmids have a common genetic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This is despite the fact that plasmids evolve rapidly and show variable characteristics within a short time span (17,34). These observations, together with the similar antimicrobial resistance patterns and the identification of these strains from the same geographical locations and the same sampling times, support the argument that the horizontal dissemination of plasmids carrying multiple antimicrobial resistance genes may have occurred between Salmonella serovar Typhimurium and Salmonella serovar Muenchen strains.…”
Section: Vol 49 2005supporting
confidence: 62%
“…This is despite the fact that plasmids evolve rapidly and show variable characteristics within a short time span (17,34). These observations, together with the similar antimicrobial resistance patterns and the identification of these strains from the same geographical locations and the same sampling times, support the argument that the horizontal dissemination of plasmids carrying multiple antimicrobial resistance genes may have occurred between Salmonella serovar Typhimurium and Salmonella serovar Muenchen strains.…”
Section: Vol 49 2005supporting
confidence: 62%
“…Within three years of its discovery, conjugative plasmids encoding OHIO-1 were found disseminated in virtually all species of the family Enterobacteriaceae on at least one ward in our medical center (28). We later showed that all of these plasmids, regardless of origin, were derived from a single progenitor (17). These observations were consistent with the lack of observable transposition of OHIO-1 (D. M. Shlaes and G. Jacoby, unpublished observations).…”
Section: Methodssupporting
confidence: 73%
“…OHIO-1 has a pI similar to that of LEN-1 but is plasmid mediated. OHIO-1 appears to have been geographically restricted within the state of Ohio (17,28,29). To better understand the evolution of this restricted resistance mechanism, we have sequenced the structural gene and its flanking sequences.…”
mentioning
confidence: 99%
“…Additionally, the RFLP patterns identified many highly conserved restriction fragments among each of the plasmids, suggesting that the plasmids may be genetically similar but that they may have evolved over time. Previous studies have shown that plasmid DNA can change rapidly (24,40). DT104 isolates of Salmonella typically carry a chromosomal integron that encodes all or a subset of the antimicrobial resistance genes (11,37).…”
Section: Discussionmentioning
confidence: 99%